Bakelite beak retrieval: a case report of a simple strategy using suture material - Daniel Xavier Lima; Claudinei Tavares Pereira; Valdinei Oliveira Rocha (African Journal of Urology)
Abstract Background The detachment of a resectoscope sheath tip during transurethral prostate resection can lead to the troubling issue of an iatrogenic-retained foreign body if not promptly identified. Various endoscopic techniques designed to prevent the necessity for open surgery are well documented in the literature. However, most of these strategies involve considerable cost or require equipment that may not always be readily available. Here, we describe a novel and simple technique for removal that does not require expensive materials. Case presentation The tip of a standard Storz 26 Fr continuous flow resectoscope inner sheath was successfully retrieved using a 2–0 polypropylene thread and a rigid cystoscope during a prostate resection procedure to treat benign hyperplasia of the gland. Addressing surgical complications, especially the removal of foreign bodies from the bladder, is often challenging, particularly when technical resources are limited. Various approaches for removing a detached resectoscope tip have been described, indicating that none offer a perfect solution. To our knowledge, this is the first report detailing the effective use of a simple surgical suture and endoscopic forceps in conjunction with a rigid cystoscope for removing a foreign body from the bladder. Conclusions The technique described here may be considered a safe, cost-effective, and relatively straightforward procedure that could be beneficial to urological surgeons, particularly when working under suboptimal conditions.